2016
DOI: 10.2106/jbjs.15.00751
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Illness Is Common Among Patients with Orthopaedic Polytrauma and Is Linked with Poor Outcomes

Abstract: Psychiatric illness was common among individuals who sustained orthopaedic polytrauma, and patients with depression had more complications. This study highlights the need for greater attention to mental health disorders in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
91
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(92 citation statements)
references
References 65 publications
1
91
0
Order By: Relevance
“…Several of these patient characteristics have been substantiated in the published literature [4][5][6][12][13][14].…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Several of these patient characteristics have been substantiated in the published literature [4][5][6][12][13][14].…”
Section: Discussionmentioning
confidence: 79%
“…Townsend and colleagues (2017) reported on characteristics of PMI + trauma patients using the Nationwide Inpatient Sample (2012) and found that 44% of trauma patients ≥ 18 years of age were PMI + across 36.5 million patients, and similarly, PMI + trauma patients were signi cantly more likely to be female, to be an average age of 61 years (vs. 56 years), and have a higher number of comorbidities compared to PMI-trauma patients [4]. In a single center study, Weinberg et al (2016) described the prevalence and characteristics of psychiatric illness among orthopedic polytrauma patients and also discovered a signi cantly higher percentage of PMI + patients (vs. PMI-) were female (38.5% vs. 23.7%) and had depression (22.3%) [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Social, economic and psychological parameters are becoming increasingly accepted as having substantial bearing on recovery after traumatic injury. Preinjury mental illness is pervasive among trauma patient populations with reported rates as high as 45% 1–8. Substance use is also ubiquitous among trauma patients 9 10.…”
Section: Introductionmentioning
confidence: 99%
“…The relatively high prevalence of mental health problems before and after surgical interventions for FGM may negatively affect treatment outcomes . This has raised the need for specialized health services that provide psychological care and counselling for girls and women living with FGM .…”
Section: Introductionmentioning
confidence: 99%